The Application of Leadership Style in School Management: A Case Study of Arusha District Tanzania - Nakija Mussa, (International Journal For Research In Educational Studies, 2023)
This study explores leadership styles in school management within the Arusha District, aiming to identify prevalent approaches, assess their practical application, and offer recommendations for successful leadership. Utilizing qualitative research, including interviews and document reviews, the study distinguishes five dominant leadership styles: Autocratic, Transactional, Transformational, Democratic, and Servant leadership. These styles reflect diverse strategies educational leaders in the Arusha District Council employ. The findings emphasize the need for flexibility and adaptability in leadership, recognizing that different schools may require varied approaches based on their unique situations and challenges. This adaptable leadership style allows schools to address specific needs, fostering a positive and supportive learning environment. The study proposes a holistic strategy for successful leadership, prioritizing training, inclusive decision-making, mentorship, effective communication, teacher professional development, and resource management while cultivating a positive school culture. Implementing these recommendations presents an opportunity to enhance education quality and overall school success in the Arusha District. This approach promotes a positive atmosphere beneficial for students and teachers, acknowledging adaptability is key to navigating challenges effectively. In essence, the study advocates for a comprehensive and dynamic leadership approach tailored to the specific context of each school within the Arusha District.